Detection of label-free cancer biomarkers using nickel nanoislands and quartz crystal microbalance - Adrián Martínez-Rivas (Dove Medical Press, 2010)
Adrián Martínez-Rivas1,2, Patrick Chinestra3,4, Gilles Favre3,4, Sébastien Pinaud1, Childérick Séverac1,2, Jean-Charles Faye3,4, Christophe Vieu1,21LAAS-CNRS; Université de Toulouse, Toulouse, France; 2Université de Toulouse, UPS, INSA, INP, ISAE; LAAS; Toulouse, France; 3INSERM U563, Université de Toulouse, CPTP, “Signalisation Cellulaire, GTPase Rho et cancers”, Toulouse, France; 4Institut Claudius Regaud, Biology Department, Toulouse, FranceAbstract: We present a technique for the label-free detection and recognition of cancer biomarkers using metal nanoislands intended to be integrated in a novel type of nanobiosensor. His-tagged (scFv)-F7N1N2 is the antibody fragment which is directly immobilized, by coordinative bonds, onto ~5 nm nickel islands, then deposited on the surface of a quartz crystal of a quartz crystal microbalance (QCM) to validate the technique. Biomarker GTPase RhoA was investigated because it has been found to be overexpressed in various tumors and because we have recently isolated and characterized a new conformational scFv which selectively recognizes the active form of RhoA. We implemented a surface chemistry involving an antibiofouling coating of polyethylene glycol silane (PEG-silane) (<2 nm thick) and Ni nanoislands to reach a label-free detection of the active antigen conformation of RhoA, at various concentrations. The methodology proposed here proves the viability of the concept by using Ni nanoislands as an anchoring surface layer enabling the detection of a specific conformation of a protein, identified as a potential cancer biomarker. Hence, this novel methodology can be transferred to a nanobiosensor to detect, at lower time consumption and with high sensitivity, specific biomolecules.Keywords: nickel nanoislands, cancer biomarkers, quartz crystal microbalance, PEG-silane, RhoA protein, nanobiosensor